PENGEMBANGAN MEDIA BELAJAR PJOK PADA MATERI SENAM LANTAI (ARTISTIK) - Zulbahri, Zulbahri; Astuti, Yuni; ., Erianti; ., Pitnawati; ., Damrah (Jurnal Ilmu Keolahragaan Undiksha, 2020)
This research is motivated by the limited development of learning media for the subjects of Physical Education, Sports and Health on floor exercise (artistic) material, especially for schools in the regions. This study aims to produce a learning media product for students and students in learning gymnastics. The subjects or samples of this research were FIK UNP students who attended basic and advanced / learning gymnastics courses with a total of 12 people for small group subject trials and 15 people for field trials. The data used in this research are qualitative and quantitative data. Qualitative data in this study is data obtained through validation from material experts, media experts, while quantitative data in this study were obtained through assessment questionnaires which were analyzed with descriptive statistics.This research was conducted using "Research and Development" (Research and Development), namely the research method used to produce certain products. The model used as a reference is the Borg & Gall development research model with 10 developments, in this study the researcher adopted the following stages: 1) Preliminary Study (research and data collection). 2) Prepare a plan and analyze the media to be made. 3) Initial product development by producing learning media with validation by media experts and material experts. 4) Conduct small group trials. 5) Product Revisions. 6) Conduct field trials. 7) Revise the final product. For this early stage research, it has only arrived at the fourth stage (4), namely the initial stage validation by media experts and material experts. Research results in the form of learning media products for practical material with a score of 3.67 with good criteria and for media with a score of 3.3 with a fairly good category.